(untitled) (International Journal of Medical and Surgical Sciences, 2020)
An exhaustive investigation is carried out on the cause of death of this pedestrian, carrying out an extensive bibliographic search taking into account the pathophysiology of trauma for this type of accident, and then making a clinical-pathological correlation of the series of events that concluded with the death of this person and its applicability in trauma services.